Respuesta :

Factorise the equation first of all.

The easiest way to do this is to find two number that add to make the middle (-8) and multiply to make the last number (-9)

Two numbers with this property are -9 and 1

So when you factorise, your equation becomes (x-9)(x+1) = 0

From these you can conclude that for the equation to be equal to 0, either

x-9= 0
So x = 9

Or
x+1 = 0
And
x= -1

Answer:

(x+1)(x-9)

Step-by-step explanation:

Break the equation: x²- 8x-9=0 into groups:

([tex]x^{2}[/tex]+x)+(-9x-9)

Factor X out of [tex]x^{2}[/tex]+x:    x(x+1)

Then Facor -9 out of (-9x-9):  -9(x-1)

This means that you can simplify these 2 equations: (x-9) & (x+1)

So your answer is: (x+1)(x-9)